Hydrogen and syngas production by catalytic biomass gasification. (1st March 2017) - Peng, W.X.; Wang, L.S.; Mirzaee, M.; Ahmadi, H.; Esfahani, M.J.; Fremaux, S.
Highlights: H2 was produced by catalytic gasification of biomass in presence of Ni/CeO2 /Al2 O3 catalysts. Ni/Al2 O3 catalyst is more effective for enhancing the H2 yield and tar cracking. Higher temperatures were significantly resulted in tar cracking and hydrogen production. An increase in residence time was caused a considerable decrease in the tar yield. Abstract: Air-steam gasification of wood residue was explored in a research scale fluidized bed. Catalytic activity of two different kinds of metal catalysts (Ni/CeO2 /Al2 O3 ) with various catalyst loadings (20, 30, and 40%) was also investigated at various residence time (20, 40, and 60 min) and gasification temperature (750, 825, and 900 °C). Non-catalytic experiments were also carried out to determine the optimum conditions for tar cracking and hydrogen/syngas production. Results were revealed that the high temperature (∼900 °C) and high catalyst loading (∼40%) are favorable for tar cracking and high-purity hydrogen production. It was also found that for a residence time of 60 min, the tar cracking at the presence of Ni/CeO2 /Al2 O3 is 196% more than that of the case without any catalyst, while at the presence of Ni/Al2 O3 it drops to 162%. Finally, the experiments were showed that Ni/CeO2 /Al2 O3 is more suitable for biomass conversion and hydrogen production than Ni/Al2 O3 .